Measuring the impacts of financial supports based on input-output analysis - Antoušková, Michaela (Univerzita Pardubice, 2010)
The article deals with an evaluation of financial supports. It focuses on the Action Plan of the Regional Development Program (AP PRK) in Southern Bohemia and specializes on tourism development. Within the 3 grant programmes supporting tourism, it analyses distribution of financial means to the regions. The disparities among the regions are measured by Gini coefficient. Moreover, using an input-output analysis, the direct and indirect impact of financial support on regional production is considered.
Keywords: input-output analysis; tourism; financial supports; regional development